Effectiveness of Behavioral Counseling with Modeling Techniques to Improve The Character Solve Everything Good and Will Succeed Through Study Leason - Nurul Ardhia Cahyuni; Wayan Tirka; I Ketut Dharsana (RedwhitePress)
This study aims to determine the effectiveness of behavioral counseling Ivan Pavlov with modeling techniques to improve the character of all the whole hog with a good finish and will succeed lesson study. This type of research is quasi-experimental with pre-test and post-test control group design. Samples were 38 students with df 37. Methods of data collection using questionnaires finish everything well and will succeed 30 items. The results of the data analysis is the value of tcount 7961>ttable 1:30 so that H0 refused and Ha accepted. So there are significant differences. It can be concluded that behavioral counseling Ivan Pavlov effective modeling techniques to improve the character of finished everything well and be successful.